Diffuse idiopathic skeletal hyperostosis: an uncommon complication in head and neck surgery - Bustos, Felipe A.; Capdeville, Felipe A.; Rappoport, Daniel A.; Zanolli, Luis F.; Valdes, Fabio; Rojas, Hugo E.; Contreras, Jose M.; Schiappacasse, Giancarlo; Madrid, Arturo J. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Diffuse idiopathic skeletal hyperostosis (DISH) is a degenerative disorder of unknown etiology that most often occurs in male patients over 50. Dysphagia is its main symptom, but they can also have dyspnea, otalgia, cough, sore throat, foreign body sensation in the pharynx, sleep apnea and glottic alterations. We present a case report and review the literature about this entity. We report a case of an oral squamous cell carcinoma that received a commando surgery and tracheostomy tube. Decanulations attempts were unsuccessful initially due to DISH. Conservative management was successful and complete rehabilitation performed, achieving decannulation 18 months after surgery. DISH can be a source of many different symptoms that may appear or be exacerbated after any surgery, and produce a postoperative complication. Conservative management is usually the best treatment, leaving surgical interventions for severe symptomatic patients. The knowledge of this entity and a high level of suspicion are very important for a proper diagnosis and management.